Analisis Kemampuan Berpikir Kritis Matematis Siswa SMA dalam Menyelesaikan Soal Cerita Ditinjau dari Self Efficacy - Evin Susanti; Reni Astuti; Muchtadi Muchtadi (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The purpose of this study was to find out more carefully students' critical thinking skills in solving word problems in terms of self-efficacy. This research is a qualitative research with a descriptive approach. . The form of research used in this study is a case study. This research was conducted at Semparuk 1 Public High School, Sambas Regency, West Kalimantan. The research subjects were 33 students in class X IPS I. Then 9 students were taken as subjects for interviews where each subject had high, medium and low self-efficacy. The data in this study are in the form of critical thinking ability test results, self-efficacy questionnaire results, and interview results. In this study, data analysis using the Miles and Huberman model was used. Activities in data analysis, namely data collection, data reduction, data display, and conclusion drawing/verification. From the results of the study it was found that students who have high self-efficacy have been able to solve Trigonometry story problems well and in accordance with the indicators of mathematical critical thinking ability, students who have moderate self-efficacy have been able to solve Trigonometry story questions poorly and have not fulfilled the four indicators of thinking ability mathematically critical, and students who have low self-efficacy are only able to say what is asked in the questions correctly, while other indicators of mathematical critical thinking skills are not resolved correctly..